Building an Integrated Food Estate to Realize Territorial Resilience in Papua - Rudiawan, Beni; Amarulla Octavian; Rizerius Eko Hadi Sancoko; Wayan Nuriada; Buddy Suseto; Martinus Dwi Arjanto Widodo; Endah Sri Rejeki (Open Access Indonesia Journal of Social Sciences, 2021)
The problem of the high social gap in Papua, which is the cause of marginalization and discrimination against the Papuan people, and the different perceptions of some Indonesians at home and abroad towards armed separatist conflicts are push factors to corner the Indonesian government. In addition, the issue of internationalization of the 1969 referendum mechanism, violations of human rights, and the management of natural resources by multinational companies that do not have an impact on improving the welfare of the Papuan people also complement the opinion of the government's failure. Against the background of these problems, this study uses a quasi-qualitative research method. We collected research data through focus group discussions (FGD), in-depth interviews, and direct discussions with various informants (academics, practitioners, bureaucracy, and community leaders), completed with literature review as secondary data. The results of this study recommend the development of an Integrated Food Estate (IFE) in stages according to customary areas in Papua, which will indirectly support the realization of territorial resilience and the Universal Defense System (Sishta). In conclusion, with all implementation of recommendations, it is hoped the completion of peaceful and prosperous Papuan people will come true.